Overview of obstetric violence in Brazil: A narrative review (Research, Society and Development, 2024)
Introduction: Obstetric violence, a severe form of gender-based violence, remains a significant issue in Brazil, reflecting inadequate and dehumanizing practices in the care of women during the perinatal cycle.  Objective: To outline a comprehensive profile of obstetric violence in Brazil. Materials and Methods: This is an narrative literature review of publications from 2014 to 2023, sourced from the Scielo, Lilacs, and PubMed databases. Using content analysis methodology, the research includes pre-analysis, exploration of the material, and interpretation of the results to provide an in-depth understanding of obstetric violence and the role of nursing in promoting humanized and abuse-free care.  Results: The findings highlight that obstetric violence in Brazil manifests in both physical and psychological forms, compromising women's autonomy and mental health. Dehumanizing practices and the lack of adequate training for healthcare professionals are identified as factors that perpetuate this violence. The research underscores the urgent need for reforms in professional training and the implementation of policies that ensure more ethical and respectful care.  Conclusions: The findings suggest the importance of a critical and informed approach to addressing obstetric violence, promoting a birthing environment that prioritizes the dignity and well-being of women.